Parenting styles and its relation with children behavioral problems - Seyede Zahra Shafipour; Ali Sheikhi; Mahshid Mirzaei; Ehsan KazemnezhadLeili (Journal of Holistic Nursing and Midwifery)
Introduction: Misbehavior and over-activity are the most problems among children. However, how to communicate with children is important and may relate to their parenting style. Parenting styles play an important role in the formation of abnormality and normal personality behavior in children. The use of adaptive styles in children can lead to many negative consequences, including behavioral problems. Objective: The aim of this study was to investigate the relationship between parenting styles and children misbehavior (internalizing and externalizing). Methods: This cross-sectional descriptive study performed with randomly selection on 741 student aged 6 to 12 first grade to fifth grade public and private schools of 1th and 2th region in the city of Rasht in 2012. The information collected tool was Baum rind parenting style questionnaire and teacher reports. The data was analyzed using descriptive and Pearson correlation and multiple linear regression method stepwise. Results: The results showed that parents of subjects with authoritative parenting style were the most (96/5%) with a mean of (SD) 41/26 ± 8/29. Also, 12/1% of children have externalizing misbehavior and 8/9% of them have internalizing problems. Results indicated that authoritative style had negative significant relationship between internalized behavior problems score (p<0.003) and externalizing problems score (p<0.020). There was a significant positive relationship between permissive style and internalized behavior problems score (p<0.006). The results of regression analysis showed that authoritative style is a negative significant predictor with all internalizing and externalizing behavior problems and permissive style is a positive significant predictor of all internalizing behavior problems. Conclusions: Authoritative parenting, with associations of control under high passionate support, creates independence and conjoint relationship between child and parents, which could characterize an important role in prevention of problems behavioral disorders of children. Also permissive style with little supervision and parental unresponsiveness towards the child's behavior could also lead to behavioral problems in children.